(untitled) (Journal on Geoinformatics, Nepal, 2013)
The cadastral system in Nepal is developing continuously with gradual speed. Cadastralsurvey started with chain survey and in due course of time, plane table survey was adopted for the survey in spite of its limitations in accuracy and time. Currently, total station has been practiced in few municipalities for this purpose. The paper focuses on the probability of modern data handling technology; Total station, Global Positioning System (GPS), Participatory GIS and Remote Sensing as the appropriate technology for the improvement of existing cadastral system of the country. Current situation of the cadastral system and the technology used, its shortcomings and the suitability of the proposed data handling technology are discussed in the paper. Nepalese Journal on Geoinformatics -12, 2070 (2013AD): 19-24